2021
DOI: 10.1016/j.freeradbiomed.2021.08.237
|View full text |Cite
|
Sign up to set email alerts
|

Serum nitrite and nitrate: A potential biomarker for post-covid-19 complications?

Abstract: Nitric oxide (NO) plays an important role in cardiovascular and immune systems. Quantification of blood nitrite and nitrate, two relatively stable metabolites of NO (generally as NO x ), has been acknowledged representing NO bioactivity partially. Dysregulation of NO x had been reported in SARS-CoV-2 infected populations, but whether patients recovered from COVID-19 disease present with restored NO x is unknown. In this study, serum NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 76 publications
1
28
0
1
Order By: Relevance
“…Hypoxia also increases the presence of protons, in a similar way as in a neutral or acidic pH, compromising the stability of ONOO − and decomposing peroxynitrous acid to form nitrates (NO 3 − ) and NO 2 − [54]. ONOO − causes the irreversible process of nitration of tyrosines in proteins, it oxidizes the thiol groups in them [56] and it also lowers the H 2 S concentration. In this sense, H 2 S is a potent gasotransmitter that is decreased in COVID-19 patients [57].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia also increases the presence of protons, in a similar way as in a neutral or acidic pH, compromising the stability of ONOO − and decomposing peroxynitrous acid to form nitrates (NO 3 − ) and NO 2 − [54]. ONOO − causes the irreversible process of nitration of tyrosines in proteins, it oxidizes the thiol groups in them [56] and it also lowers the H 2 S concentration. In this sense, H 2 S is a potent gasotransmitter that is decreased in COVID-19 patients [57].…”
Section: Discussionmentioning
confidence: 99%
“…Both are evaluated in vivo with serum NO metabolites; nitrite and nitrate. Patients who recovered from COVID-19 showed lower nitrite and nitrite/nitrate ratio and higher nitrate levels than uninfected subjects [ 32 ]. COVID-19 causes SARS, where nitrate+nitrite concentrations were higher in patients with SARS who died, as reported by Sittipunt et al [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al measured the nitrate and nitrite levels of 109 recovered adult COVID-19 patients 4 months after recovery and compared them to those of 166 uninfected adults. Lower nitrite and nitrite/nitrate, and higher nitrate levels were found among the recovered patients, indicating according to the authors long-lasting eNOS damage after COVID-19 infection [ 96 ]. Fasted nitrate levels have been used as an indicator of eNOS function, but since the work of Lauer et al, multiple studies have found that circulating nitrite and nitrate/nitrite ratios are a more accurate indication of eNOS dysfunction; thus, the lower nitrite levels in both studies are a clear indicator of eNOS dysfunction [ 97 ].…”
Section: Severe Covid-19 Clinical Outcomesmentioning
confidence: 99%